ANALISIS KESEHATAN BANK MANDIRI SYARIAH - Abdul Rauf Chaerudin; Rida Aulia; Nabila Zullaiqa; Nadhira Zakiyah (Jurnal Bina Bangsa Ekonomika, 2024)
The health of a bank can be seen from the bank's financial statements. The method that can be used in assessing bank performance according to Bank Indonesia regulation Number 13/1/PBI/2011 in its assessment uses the RGEC method (Risk Profile, Good Corporate Governance factor, Earning factor and Capital factor).        This study aims to obtain information about the health of the bank based on the annual report of Bank Mandiri Syariah. This study uses a qualitative method with a descriptive approach, the data used is the financial report data of Bank Mandiri Syariah.        The results of the bank's health assessment include the following, Assessment of the Risk Profile factor using the NPF ratio and FDR ratio is in the healthy category. This illustrates that Bank Syariah Mandiri has good risk management. The factor of Good Corporate Governance using self-assessment contained in the report on the implementation of Good Corporate Governance received a very healthy category, this reflects that the bank has implemented the principles of Good Corporate Governance well and has maintained it for the last 5 years. Earning factor using the ratio of NOM, ROA, ROE, and BOPO received a fairly healthy rating, this reflects inadequate profitability, earnings that do not meet targets and require immediate profit performance improvements to ensure the continuity of the bank's business. The Capital Factor received a very healthy category, this reflects that the bank has very adequate quality and capital adequacy relative to its risk profile, which is accompanied by very strong capital management in accordance with the characteristics, business scale, and complexity of the bank's business.         The soundness level of Bank Syariah Mandiri shows that the predicate of the bank's health is in accordance with the standards set by the OJK. Bank Syariah Mandiri’s financial ratios increased and overall only received a healthy predicate